Hybridization patterns between two marine snails, Littorina fabalis and L. obtusata. Issue 3 (21st January 2020) - Costa, Diana; Sotelo, Graciela; Kaliontzopoulou, Antigoni; Carvalho, João; Butlin, Roger; Hollander, Johan; Faria, Rui
Abstract: Characterizing the patterns of hybridization between closely related species is crucial to understand the role of gene flow in speciation. In particular, systems comprising multiple contacts between sister species offer an outstanding opportunity to investigate how reproductive isolation varies with environmental conditions, demography and geographic contexts of divergence. The flat periwinkles, Littorina obtusata and L. fabalis (Gastropoda), are two intertidal sister species with marked ecological differences compatible with late stages of speciation. Although hybridization between the two was previously suggested, its extent across the Atlantic shores of Europe remained largely unknown. Here, we combined genetic (microsatellites and mtDNA) and morphological data (shell and male genital morphology) from multiple populations of flat periwinkles in north‐western Iberia to assess the extent of current and past hybridization between L. obtusata and L. fabalis under two contrasting geographic settings of divergence (sympatry and allopatry). Hybridization signatures based on both mtDNA and microsatellites were stronger in sympatric sites, although evidence for recent extensive admixture was found in a single location. Misidentification of individuals into species based on shell morphology was higher in sympatric than in allopatric sites. However, despite hybridization, species distinctiveness based on this phenotypic trait together with male genital morphology remained relatively high. The observed variation in the extent of hybridization among locations provides a rare opportunity for future studies on the consequences of different levels of gene flow for reinforcement, thus informing about the mechanisms underlying the completion of speciation. Abstract : The flat periwinkles, Littorina obtusata and L. fabalis (Gastropoda), comprise an interesting system to study how reproductive barriers evolve during (ecological) speciation with gene flow. In this study, we characterized the patterns of hybridization between the two intertidal sister species across multiple populations in the Iberian Peninsula, combining genetic and morphological data. By contrasting geographic settings of divergence, an extensive variation of hybridization among locations was found, opening doors to further studies on reinforcement and its role in speciation.